Meningkatkan Penguasaan Konsep Sains Menggunakan Model Problem Based Learning Kelas V Di Sekolah Dasar - M. Habib Ridho A.R; Ramdhan Witarsa; Musnar Indra Daulay (Politeknik Kampar, 2023)
The background of this research is the low mastery of science concepts for fifth grade students of SDN 008 Salo Timur. This study aims to improve the mastery of science concepts for fifth grade students of SDN 008 Salo Timur. This research is a class follow-up study, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this study were 1 teacher and 29 students, while the object was using a problem based learning model to improve students' mastery of science concepts. The research instrument consisted of a teacher activity observation sheet and an observation sheet for student activities during the learning process using a problem based learning model. While the data analysis technique used is descriptive qualitative and quantitative analysis. Based on the results of research that has been carried out through 2 cycles, at the second meeting of the first cycle the classical mastery of mastery of science concepts is only 24, 13% in the low category and the average learning value is only 67.03 in the medium category. It is known that there was an increase in students' mastery of science concepts after improvements were made in the second cycle of meeting 2, the results of classical mastery of students' mastery of science concepts were 86.20% in the very high category and the average student learning score was 80.55 in the high category. Based on the results of this study, it is shown that if a problem based learning model is used, it can increase the mastery of science concepts for students of class V 008 East Salo.